STANDAR MUTU INTERNASIONAL ISO DALAM PENDIDIKAN: INTEGRASI ISO 9001:2015 DAN ISO 21001:2018 UNTUK PENGUATAN SISTEM PENJAMINAN MUTU LEMBAGA PENDIDIKAN - Samsul Hadi; Subandi Subandi; Deden Makhbuloh; Ahmad Fauzan (Jurnal Manajemen Pendidikan, 2026)
This study is motivated by the increasing need for educational institutions to develop a quality assurance system that is not merely oriented toward administrative compliance but also strengthens governance, academic services, learner satisfaction, accountability, and continuous improvement. This study aims to analyze the integration of ISO 9001:2015 and ISO 21001:2018 in strengthening the quality assurance system of educational institutions, particularly in relation to internal quality assurance systems, national accreditation, quality culture, and educational values. This research employed a qualitative approach with an integrative literature review design by analyzing scholarly articles, ISO standard documents, quality assurance regulations, and relevant literature on educational quality management. The findings indicate that ISO 9001:2015 serves as a generic foundation for quality management systems based on process approach, risk-based thinking, performance evaluation, and continual improvement, while ISO 21001:2018 provides a more specific orientation for educational organizations by positioning learners, beneficiaries, curriculum, learning processes, assessment, accessibility, and stakeholder satisfaction at the center of quality management.